The psychometric properties of the Russian version of the MacNew Heart Disease Health-related Quality of Life Scale in patients undergoing coronary artery bypass grafting surgery. (2013) - Geulayov, Galit; Oldridge, Neil; Ziv, Arnona; Novikov, Ilia; Drory, Yaacov; Dankner, Rachel
No abstract available